Long-Term Suitability of Left Gastric Artery Inflow for Arterial Perfusion of Living Donor Right Lobe Grafts - Judyta A. Lipinska; Johnny Wang; Joseph N. Carey; Aaron A. Ahearn; Yuri S. Genyk (Case Reports in Transplantation)
Poorer than expected, living donor liver transplant outcomes are observed after recipient graft artery thrombosis. At grafting, the risk for later thrombosis is high if a dissected hepatic artery is used for standard reconstruction. Surgeon diagnosis of dissection requires nonstandard management with alternative technique in addition to microvascular expertise. Intimal flap repair with standard reconstruction is contingent on basis of a redo anastomosis. It is a suboptimal choice for living donor transplantation. Achieving goal graft arterial perfusion at first revascularization is crucial for superior outcomes. Managing dissection at grafting with nonstandard left gastric artery reconstruction is unreported. Our experience is limited, but this is our preferred alternative technique to standard hepatic artery reconstruction complicated by dissection. Here, we describe our two-case experience with left gastric arterialized grafts for management of dissection. Our living donor graft recipients with alternatively arterialized grafts are now 6- and 2-years posttransplant.